Eva y su aporte en las metodologías activas de la carrera de Educación Básica de la Universidad Técnica de Babahoyo, periodo diciembre 2022-abril 2023 - Salvatierra Arroyo, Joselin Mercedes (2023)
The pandemic has significantly affected education, leading to the implementation of various technologies and active methodologies to ensure the teaching process. In this context, virtual learning environments (VLE) have emerged as a fundamental tool for teachers in the Basic Education career at the Technical University of Babahoyo during the period December 2022-April 2023. The main objective of this descriptive and quantitative study was to determine the contribution of the EVA in the active methodologies of the Basic Education career at this university, with the participation of 122 students in a survey. The results indicate that there is a positive tendency towards the use of EVA and the application of active methodologies by teachers in the Basic Education course. This suggests that students have greater exposure to these tools and methodologies in the classroom, which may be beneficial to their learning process. The study identified that forums, assignments and some research are the most common forms of EVA use in the university's Moodle tool. However, to maximize the impact of EVAs in the teaching process, it is recommended to provide more training and education opportunities for teachers in the effective use of technological tools and active methodologies in the classroom. This would allow them to be more confident in their ability to use these tools and maximize their impact on the teaching process.